The Opportunities To Have Own Home in Banda Aceh City - Yasrizal Yasrizal (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
As we know that the development of infrastructure, especially housing problems is really needed by everyone and had so much built by developers both inside the city and outside the city. This rmesidential development ranging from the type, design and technical specifications are varied, it is intended to be accessible by consumers. Although developers already provide some conveniences such as the ability to repay in accordance with the selected type, there are still plenty of civil servant (PNS) as well as those working in the private sector has not been able to buy/own their own home on the grounds of various considerations interests respectively. Explanatory variables used in this model consists of a variable income, number of household members, gender, education level, employment sector, age and marital status will affect the probability of households to own their own home.The data used is the National Socio-Economic Survey 2011, which contains the results of a survey conducted by BPS. This thesis focuses on the area of Banda Aceh as well as using the logit model estimation. The result of calculations show that the proportion of households in the city of Banda Aceh who own their own home around 53.83%, with the proportion who are not self owned approximately 46.17%. The analysis showed that the variables household size and age significantly affect the chances of having their own home with a significance level of 5%.Keywords: Home Ownership, Logit Model